2009
DOI: 10.1117/12.840217
|View full text |Cite
|
Sign up to set email alerts
|

Study of the response time of MR dampers

Abstract: Response time is an important parameter which determines the applied fields and practical vibration reduction effects of magnetorheological (MR) dampers. However, up to now, only a few papers discuss the test and analysis of response times. In this paper, the response time of a large-scale MR damper at different velocities and currents was firstly tested. Then, the transient magnetic field excited by the time-variant excitation current was simulated by finite element method (FEM). Based on the variation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Guan et al . experimentally investigated the response time of a large‐scale MR damper at different velocities (in the range 1–4 cm/s) and currents (0.0–1.2 A), highlighting the electromagnetic response as the predominant factor influencing such delays, also demonstrating that lesser eddy current leads to a fast response. They define the response time as the time span needed to achieve 63% of the desired total variation of the force in the damper.…”
Section: Introductionmentioning
confidence: 99%
“…Guan et al . experimentally investigated the response time of a large‐scale MR damper at different velocities (in the range 1–4 cm/s) and currents (0.0–1.2 A), highlighting the electromagnetic response as the predominant factor influencing such delays, also demonstrating that lesser eddy current leads to a fast response. They define the response time as the time span needed to achieve 63% of the desired total variation of the force in the damper.…”
Section: Introductionmentioning
confidence: 99%
“…Eddy currents in the coil core Guan et al (2009) found out that between the course of electric current and the course of MR damper force, there is a time lag. They explained this lag as a result of eddy currents induced in the magnetic circuit.…”
Section: Inductance Of Mr Damper Coilmentioning
confidence: 99%
“…18 The response time is often neglected in simulations, 19 but in Strecker et al, 20 12 and Koo et al 21 experimentally proved that the use of current controller instead of the voltage power source significantly reduces the rise time of the current to the desired value. Eddy currents in the magnetic circuit: Guan et al 22 noticed that the MR damper force rise, after the step of electric current to the coil, is much longer compared to the course of electric current. This delay was explained as a result of eddy currents, which are generated during fast changes of electric current in the coil.…”
Section: Introductionmentioning
confidence: 99%